2000
DOI: 10.1507/endocrj.47.317
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Proliferative Potential, Apoptosis and Bcl-2 Protein Expression in Cytotrophoblasts and Syncytiotrophoblast in Human Placenta over the Course of Pregnancy.

Abstract: Abstract.In order to evaluate placental trophoblast proliferation and apoptosis during pregnancy, we investigated proliferating cell nuclear antigen (PCNA) expression, apoptosis and Bcl-2 protein expression in the human placenta using avidin/biotin immunoperoxidase method to examine PCNA and Bcl-2 protein expression, and TUNEL method to assess apoptosis. The appearance of apoptotic cells in very early term placental trophoblasts was also examined by transmission electron microscopy.PCNA was immunolocalized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
(34 reference statements)
1
36
0
1
Order By: Relevance
“…First-trimester trophoblast cells are highly proliferative while third trimester trophoblast cells are not. 32 Infection with ZIKV was further confirmed by transmission electron microscopy, which showed the presence of ZIKV within the cells (Fig. 1C).…”
Section: Effectofzikvonfirst-trimestertrophoblast Cellsmentioning
confidence: 68%
“…First-trimester trophoblast cells are highly proliferative while third trimester trophoblast cells are not. 32 Infection with ZIKV was further confirmed by transmission electron microscopy, which showed the presence of ZIKV within the cells (Fig. 1C).…”
Section: Effectofzikvonfirst-trimestertrophoblast Cellsmentioning
confidence: 68%
“…The majority of the apoptotic cells were found in the trophoblast layer; and no significant differences were observed between placentas obtained after vaginal delivery compared to Cesarean section-suggesting that apoptosis was not caused by vaginal delivery. 50 Ishihara et al 51 also used TUNEL assays to demonstrate that apoptosis in the syncytiotrophoblast cells remained low at term, whereas, for the cytotrophoblast cells, apoptosis reached its nadir during the second trimester and then increased threefold to fourfold at term. 51 Magee et al 52 confirmed significant levels of TUNEL-positive cells and proapoptotic proteins (including Fas, FasL, caspase, and PARP) in term human placentas; interestingly, the apoptosis markers were significantly decreased in placentas from pregnancies complicated by gestational diabetes.…”
Section: Trophoblast Cells and Apoptosismentioning
confidence: 99%
“…50 Ishihara et al 51 also used TUNEL assays to demonstrate that apoptosis in the syncytiotrophoblast cells remained low at term, whereas, for the cytotrophoblast cells, apoptosis reached its nadir during the second trimester and then increased threefold to fourfold at term. 51 Magee et al 52 confirmed significant levels of TUNEL-positive cells and proapoptotic proteins (including Fas, FasL, caspase, and PARP) in term human placentas; interestingly, the apoptosis markers were significantly decreased in placentas from pregnancies complicated by gestational diabetes. As described by Zhou et al, 53 the levels of apoptosis (as indicated by TUNEL assays) were fivefold higher in term placentas from women in labor compared to those not in labor, and 15-fold higher in placentas from women whose pregnancies were complicated by preterm labor.…”
Section: Trophoblast Cells and Apoptosismentioning
confidence: 99%
“…Moreover, members of the Bcl-2 family are differently expressed during the gestational period in cytotrophoblasts and syncytiotrophoblasts (Ishihara et al 2000, De Falco et al 2001, with alterations in their expression being described in some pathophysiological situations such as pre-eclampsia, IUGR and hyperglycaemia (Sgarbosa et al 2006, Longtine et al 2012b, Borzsonyi et al 2013. Therefore, it seems that anomalies in cell death regulation through the mitochondrial pathway of apoptosis may be involved in pregnancy complications.…”
Section: -Ag Induces Apoptosis In Bewo Cellsmentioning
confidence: 99%